2003
DOI: 10.1093/emboj/cdg550
|View full text |Cite
|
Sign up to set email alerts
|

Mutations occur in the Ig S  region but rarely in S  regions prior to class switch recombination

Abstract: Nucleotide substitutions are found in recombined Ig switch (S) regions and also in unrecombined (germline, GL) Sm segments in activated splenic B cells. Herein we examine whether mutations are also introduced into the downstream acceptor S regions prior to switch recombination, but ®nd very few mutations in GL Sg3 and Sg1 regions in activated B cells. These data suggest that switch recombination initiates in the Sm segment and secondarily involves the downstream acceptor S region. Furthermore, the pattern and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
69
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 52 publications
(115 reference statements)
14
69
1
Order By: Relevance
“…However, compared to the input DNA segments, S associated with hyperacetylated H3 and H4 did not have a higher frequency of mutations in cells stimulated with either LPS or LPS plus IL-4 (Table 2). Overall, both the input and immunoprecipitated S region had frequencies of mutation that are similar to those reported in the literature (33,36,40,41), suggesting that the S region is constitutively acetylated and thus accessible to AID once AID is induced (Fig. 1).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…However, compared to the input DNA segments, S associated with hyperacetylated H3 and H4 did not have a higher frequency of mutations in cells stimulated with either LPS or LPS plus IL-4 (Table 2). Overall, both the input and immunoprecipitated S region had frequencies of mutation that are similar to those reported in the literature (33,36,40,41), suggesting that the S region is constitutively acetylated and thus accessible to AID once AID is induced (Fig. 1).…”
Section: Resultssupporting
confidence: 83%
“…1 and 2B), also correlating with the decrease of S␥3 GLT at the same time (51). Thus, the density of RNAP II, associated with the parts of the ␥3 and ␥1 S regions that frequently undergo recombination (33,36,41), was consistent with the sterile transcription of those S regions as reported in the literature (40,51,52) and probably provides a rough measure of the rate of transcription of recipient S regions (34). (Fig.…”
Section: Resultssupporting
confidence: 77%
“…Large ISDs typically are assayed by activating B cells in culture to switch to a particular C H and then generating hybridomas and assaying for ISD in IgM-producing hybridomas that have not undergone bona fide CSR (11,12). Most such studies have found that large ISDs occur far more frequently in Sμ than in downstream target S regions (6,12,13). The almost complete absence of detectable ISDs or SHMs in downstream S regions in prior studies (6,12) led to the proposal that AID targeting in Sμ is required to promote AID targeting of downstream S regions (6).…”
mentioning
confidence: 99%
“…Most such studies have found that large ISDs occur far more frequently in Sμ than in downstream target S regions (6,12,13). The almost complete absence of detectable ISDs or SHMs in downstream S regions in prior studies (6,12) led to the proposal that AID targeting in Sμ is required to promote AID targeting of downstream S regions (6). However, it is possible that absence of downstream ISD or SHM in those studies might reflect, in part, IgM + hybridomas arising from B cells not fully activated for CSR (2,12).…”
mentioning
confidence: 99%
“…Point mutations occurring close to the recombination junction are supposedly generated during the resolving step of CSR, given that they are generally more frequent and mostly affect GC residues, in comparison with point mutations in the germline Sμ region, which exhibit a pattern similar to SHM in V regions and thus likely involve a different mechanism (28,29). A lower number of mutations around the Sμ-Sα junctions (±15 bp) has been reported in patients with Artemis deficiency and Ataxia-telangiectasia compared with controls, suggesting that DNA ends are not normally processed in these individuals (27).…”
Section: Position Of Sμ and Sα Breakpoints In Switchmentioning
confidence: 99%